2017
DOI: 10.1016/j.jsat.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Why aren't physicians prescribing more buprenorphine?

Abstract: Background & Objective Buprenorphine is an underutilized pharmacotherapy that can play a key role in combating the opioid epidemic. Individuals with opioid use disorder (OUD) often struggle to find physicians that prescribe buprenorphine. Many physicians do not have the waiver to prescribe buprenorphine, and a large proportion of physicians that are waivered do not prescribe to capacity. This study aimed to quantitatively understand why physicians do not utilize buprenorphine for the treatment of OUD more freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
225
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(238 citation statements)
references
References 38 publications
(39 reference statements)
10
225
3
Order By: Relevance
“…18 Another study found that non-waivered physicians were more likely to report a lack of belief in the efficacy of buprenorphine, concerns about being overwhelmed by requests for treatment, and a lack of education. 19 This intervention, which provided practices with additional support from the institution in the form of recovery coaches, education, and input from an addiction specialist at bimonthly conferences, was effective at increasing the frequency of prescribing for both buprenorphine and naltrexone.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another study found that non-waivered physicians were more likely to report a lack of belief in the efficacy of buprenorphine, concerns about being overwhelmed by requests for treatment, and a lack of education. 19 This intervention, which provided practices with additional support from the institution in the form of recovery coaches, education, and input from an addiction specialist at bimonthly conferences, was effective at increasing the frequency of prescribing for both buprenorphine and naltrexone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the substantial growth in the number of providers with a DEA waiver, access to treatment remains difficult for many people, especially those who live in rural areas . Numerous studies show that many waivered physicians are not using their waiver to its full extent or at all, contributing to the lack of treatment access across the country . Providers with a DEA waiver frequently report challenges and barriers to incorporating this service into their practice; however, despite these challenges, many physicians report being able to successfully add and provide MAT services to their practices.…”
mentioning
confidence: 99%
“…6 Numerous studies show that many waivered physicians are not using their waiver to its full extent or at all, contributing to the lack of treatment access across the country. [7][8][9] Providers with a DEA waiver frequently report challenges and barriers to incorporating this service into their practice [10][11][12] ; however, despite these challenges, many physicians report being able to successfully add and provide MAT services to their practices. The purpose of this study, to our knowledge the first of its kind, was to identify and interview physicians who are providing MAT to a large number of patients to learn strategies and best practices for adding and providing MAT in rural areas.…”
mentioning
confidence: 99%
“…As such, one of the priorities of the CA H&S implementation has been to develop a larger cadre of buprenorphine prescribers. Once providers are waivered, they then need more support to promote active and expanded involvement in prescribing buprenorphine for OUD (Huhn & Dunn, 2017;Hutchinson, Catlin, Andrilla, Baldwin, & Rosenblatt, 2014).…”
Section: Increasing the Number And Capacity Of Waivered Prescribersmentioning
confidence: 99%